Pengembangan Sistem Informasi Pemantauan Pasien Isolasi Mandiri COVID-19 berbasis Website (Studi Kasus : Ponkesdes Jeru Turen) - Alvin Naufal Wahid; Indriati Indriati; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
COVID-19 is short for Corona Virus Disease 2019, the designation was coined by the WHO (World Health Organization). COVID-19 is a newly discovered virus that attacks the human immune system, so humans exposed to the virus can experience chronic illness and even death. The ferocity of this virus and its very rapid spread have caused a global pandemic that has not ended until now, including in Indonesia. Several measures have been taken to ward off the virus, including the discovery of a vaccine. However, it will still take a long time to completely stop the spread of the virus. The symptoms experienced by people with COVID-19 vary, ranging from severe to those without experiencing any symptoms. Patients with severe symptoms require intensive care in the hospital, while those with mild or no symptoms can self-isolate at home. The development of a Website-Based COVID-19 Self-Isolation Patient Monitoring Information System (Case Study: Jeru Turen Village Health Center) aims to facilitate monitoring of COVID-19 self-isolation patients to be more effective. This system was developed using the Waterfall method, and uses PHP, HTML, CSS, MySQL, and JavaScript technologies and uses the Laravel framework. This system has been tested using White Box Texting for unit and integration testing, and Black Box Testing for validation testing which produces 100% Passed results.